Citizenship, civic education and politics: The education policy context for young Australian citizens - Haigh, Y.; Murcia, Karen; Norris, L. (Routledge, 2014)
Citizenship education in Australia is embedded throughout the school curriculum. Despite a coherent policy context for the inclusion of citizenship and civic education at all levels of schooling, the links between education and civic minded citizens are tenuous. This paper explores these connections by drawing on the views of participants in an international community service program between Western Australia and Tanzania. By situating the interview data in relation to the policy goals, the paper argues that the current policy framework 'sanitises' the political nature of modern citizenship. The results from this study demonstrate that students have little understanding of the connections between the civic, the social and the political realms of citizenship. These results suggest that the current policy context does not adequately prepare young people to position themselves in the political realm.